On Thu, Oct 13, 2016, at 18:15, Steven D'Aprano wrote:
> Consider the analogy with f(*t), where t = (a, b, c). We *don't* have:
>     f(*t) is equivalent to f(a); f(b); f(c)

I don't know where this "analogy" is coming from.

f(*t) == f(a, b, c)
[*t] == [a, b, c]
{*t} == {a, b, c}

All of this is true *today*.

t, u, v = (a, b, c), (d, e, f), (g, h, i)
f(*t, *u, *v) == f(a, b, c, d, e, f, g, h, i)
[*t, *u, *v] == [a, b, c, d, e, f, g, h, i]

> > is very confusing, from what I understand: what does the `*` even mean
> > here.
> Indeed. The reader may be forgiven for thinking that this is yet another 
> unrelated and arbitrary use of * to join the many other uses:

How is it arbitrary? 

> - mathematical operator;
> - glob and regex wild-card;
> - unpacking;

This is unpacking. It unpacks the results into the destination.

There's a straight line from [*t, *u, *v] to [*x for x in (t, u, v)].
What's surprising is that it doesn't work now.

I think last month we even had someone who didn't know about 'yield
from' propose 'yield *x' for exactly this feature. It is intuitive - it
is a straight-line extension of the unpacking syntax.

> - import all
> - and now yield from
Python-ideas mailing list
Code of Conduct: http://python.org/psf/codeofconduct/

Reply via email to